Business Model Canvas : Smart Dustbin / Mohammad Muaz Nordin - Nordin, Mohammad Muaz (2020)
In my new product development, I have introduced a product that is an automatic dustbin that can notify user after the dustbin is full. This product is given a name “Smart Dustbin”. Business model canvas is a template for strategic management and lean startups in order to develop new business models or document existing ones. It is a visual chart with elements that describe the value proposition, infrastructure, clients, and finances of a company or product. The canvas is categorized into nine element which is key partners, key activities, value proposition, customer relationship, customer segment, key resources, distribution channel, cost structure and revenue stream. The advantage of the canvas is it helps clients to communicate why they should be doing business with you. It helps to focus on what your business is doing, and how it will continue to be successful in the future. So, in this report I will explain more about each of the element in business model canvas and related it with my new product development’s business